Evolutionary adaptations of biofilms infecting cystic fibrosis lungs promote mechanical toughness by adjusting polysaccharide production - Kristin Kovach (Nature Portfolio, 2017)
Evolution: Toughening up biofilms in lungs Bacteria in lungs of people with cystic fibrosis can evolve through decades to build a tough biofilm that resists the body’s defences. Vernita Gordon and colleagues at the University of Texas, with co-workers in Europe, examined biofilms cultured from lung samples taken from patients at intervals over many years. The infecting bacterial populations had steadily evolved to increase production of specific carbohydrate components of the biofilms. The researchers found that increasing production of one carbohydrate component strengthens the biofilms, most likely due to the carbohydrate being crosslinked by protein molecules. The investigation suggests that the mechanics of the carbohydrate-protein network protects the biofilms from being broken into smaller pieces that can be engulfed by defensive cells called phagocytes. This new insight into the evolution of mechanical toughness complements the previously observed evolution of increasing chemical protection. Understanding these processes will assist efforts to combat them.